Local Wisdom and Karst Spring Management in Playen District, Gunungkidul Regency, Indonesia - Indra Agus Riyanto; Aditya Rizky Pratama; Hafidz Bachtiar; Nanang Ahmad Fauzi; Margaretha Widyastuti; Aprilia Nur Widiyastuti; Novita Rahmawati (USN Kolaka, 2020)
For the population of Playen District, Gunungkidul Regency, karst springs serve as the primary water sources because surface rivers are rare in karst areas and, if present, the quality of their water is reportedly less than that of the springs. In the spring water utilization, local wisdom is incorporated into the management and has so far contributed to sustainability. Since only a few studies have examined local wisdom and its correlation with changes in spring management pattern, this research initiates the provision and dissemination of information on karst spring management that is applicable elsewhere. It was designed to scrutinize the local wisdom and regulatory measures implemented at many springs in Playen District. Detailed data were obtained by in-depth interviews with four key informants responsible for managing springs block 1 (Gedad, Grunggung, and Karangkulon Springs), 2 (Banyusoco and Sungai Oyo), 3 (Dung Poh, Nganding, Umbul, and Jambe), and 4 (Ngrunggo and Ngrasih). Through qualitative descriptive analysis, the research found that the laying of offerings at springs in blocks 1 and 2 during traditional celebratory ceremonies had been abandoned, but cleaning activities at and around these springs as part of the local wisdom sustained. In the context of utilization, the spring management had changed from direct manual withdrawal to indirect systematized one that used pipes with gravitational water flow system (block 1) to distribute spring water to villagers’ houses (block 2). On the contrary, local wisdom like offerings and cleaning activities at and around the springs in blocks 3 and 4 was preserved. Their management had changed from manual extraction to gas-fueled water pumping systems, which were later replaced with electricity-powered pumps (block 3), and to indirect withdrawal through pipelines with pump-generated flows (block 4). To manage the springs in all blocks and their sustainable utilization, the people of the district still adopt local wisdom. Besides, they no longer collected water directly at springs but have switched to water distribution technology like pumps and pipelines instead.